DJ-1 Regulates Microglial Polarization Through P62-Mediated TRAF6/IRF5 Signaling in Cerebral Ischemia-Reperfusion - Wang, Tingting; Zhao, Na; Peng, Li; Li, Yumei; Huang, Xiaohuan; Zhu, Jin; Chen, Yanlin; Yu, Shanshan; Zhao, Yong (Frontiers in Cell and Developmental Biology, 2020)
The polarization of microglia/ macrophage, the resident immune cells in the brain, plays an important role in the injury and repair associated with ischemia-reperfusion (I/R). Previous studies have shown that DJ-1 has a protective effect in cerebral I/R. We found that DJ-1 regulates the polarization of microglial cells/macrophages after cerebral I/R and explored the mechanism by which DJ-1 mediates microglial/macrophage polarization in cerebral I/R. Middle cerebral artery occlusion/reperfusion (MCAO/R) and oxygen and glucose deprivation/reoxygenation (OGD/R) models were used to simulate cerebral I/R in vivo and in vitro, respectively. DJ-1 siRNA and the DJ-1-based polypeptide ND13 were used to produce an effect on DJ-1, and the P62-specific inhibitor XRK3F2 was used to block the effect of P62. Enhancing the expression of DJ-1 induced anti-inflammatory (M2) polarization of microglia, and the expression of the anti-inflammatory factors IL-10 and IL-4 increased. Interference with DJ-1 expression induced pro-inflammatory (M1) polarization of microglia/ macrophage, and the expression of the proinflammatory factors TNF-α and IL-1β increased. DJ-1 inhibited the expression of P62, impeded the interaction between P62 and TRAF6, and blocked nuclear entry of IRF5. In subsequent experiments, XRK3F2 synergistically promoted the effect of DJ-1 on microglial/ macrophage polarization, further attenuating the interaction between P62 and TRAF6.